Застосування вуглецевих та мінеральних сорбентів для очищення стічних вод молокопереробних підприємств - Гивлюд, Анна; Сабадаш, Віра (Видавництво Львівської політехніки, 2013)
The present article substantiates the theoretical bases of adsorption of lactic acid on mineral and carbon adsorbents. Monitoring of wastewater contaminated with wastes of dairy plants, estimation of quantities, peculiarities of localization and estimation of toxicological impacts on the environment was carried out. The existing theoretical apparatus for adsorption processes description was analyzed. Adsorption process mechanism and methods for identification of experimental data to theoretical models was developed. Sorption capacity of zeolite to lactic acid in static conditions was experimentally investigated. Influence of acidity on equilibrium and speed of absorption of lactic acid was determined. Experimental data and theoretical models of adsorption were identified. Adsorption capasity of adsorbents was set. It has been established that carbon adsorbents are more selective to lactic acid then zeolites.
Keywords: цеоліт; активоване вугілля; молочна кислота; стічні води; зовнішня дифузія